Analisis Tantangan Pembangunan Terusan Kra: Mengapa Proyek Strategis Ini Sulit Direalisasikan - Arianto Arianto; Seniwati Seniwati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The plan for the construction of the Kra Canal has emerged since 1977, initiated by King Narai. The Kra Canal will connect the Gulf of Thailand and the Andaman Sea, making it an alternative to the congested and vulnerable Strait of Malacca. Despite its great potential and benefits and having been planned for a long time, the canal has yet to be built. This paper aims to discuss the reasons behind the difficulties in constructing the Kra Canal. The method used in this paper is qualitative descriptive by conducting library research. The theories applied are Security Dilemma and Maritime Diplomacy. The data used are secondary data sourced from books, journals, credible official news, and relevant trustworthy websites. The findings indicate that there are complex geopolitical and economic aspects. Major challenges include high costs, risks of damage, environmental concerns, and Thailand’s unstable internal political situation. The presence of the Kra Canal has the potential to complicate the security situation in the Southeast Asian region with the involvement of major powers such as China, India, and the United States.